Lack of association between gene polymorphisms of Angiotensin converting enzyme, Nod-like receptor 1, Toll-like receptor 4, FAS/FASL and the presence of Helicobacter pylori-induced premalignant gastric lesions and gastric cancer in Caucasians - Kupcinskas Juozas; Wex Thomas; Bornschein Jan; Selgrad Michael; Leja Marcis; Juozaityte Elona; Kiudelis Gediminas; Jonaitis Laimas; Malfertheiner Peter (BMC, 2011)
Abstract Background Several polymorphisms of genes involved in the immunological recognition of Helicobacter pylori and regulating apoptosis and proliferation have been linked to gastric carcinogenesis, however reported data are partially conflicting. The aim of our study was to evaluate potential associations between the presence of gastric cancer (GC) and high risk atrophic gastritis (HRAG) and polymorphisms of genes encoding Angiotensin converting enzyme (ACE), Nod-like receptor 1 (NOD1), Toll-like receptor 4 (TLR4) and FAS/FASL. Methods Gene polymorphisms were analyzed in 574 subjects (GC: n = 114; HRAG: n = 222, controls: n = 238) of Caucasian origin. ACE I/D (rs4646994), NOD1 796G>A (rs5743336), TLR4 3725G>C (rs11536889), FAS 1377G>A (rs2234767), FAS 670A>G (rs1800682) and FASL 844T>C (rs763110) were genotyped by different PCR approaches and restriction fragment length polymorphism analysis. Results Frequencies of genotypes in our study are similar to the data reported on subjects of Caucasian ethnicity. There was a tendency for NOD1 796G/G genotype to be associated with increased risk of HRAG (62.4% vs. 54.5% in controls, p = 0.082). FAS 670G/G genotype was more frequent in HRAG when compared to controls, 23.9% and 17.2% respectively, however it failed to reach significance level (p = 0.077). We did not find any significant associations for all polymorphisms in relation to GC or HRAG. NOD1 796G>A and TLR4 3725G>C gene polymorphisms were also not associated with Helicobacter pylori infection. Conclusions ACE, NOD1, TRL4 and FAS/FASL gene polymorphisms are not linked with gastric carcinogenesis in Caucasians, and therefore they should not be considered as potential biomarkers for identifying individuals with higher risk for GC.